Exploring the Role of Chinese Variable Logo Fonts in University Branding Strategies: A Case Study at Xi'an Eurasian University - Jian, Pan; Yitao, Zhang; Romainoor , Nurul Hanim Binti Md (Journal of Ecohumanism, 2025)
This study investigates the role of Chinese variable logo fonts in the branding strategy of Xi'an Eurasian University. As dynamic branding elements become increasingly important in higher education, this research examines the specific scenarios where these fonts are employed. Using qualitative methods, including in-depth interviews with 10 respondents (brand designers, university representatives, and department heads), the study analyzes the patterns and contexts of font usage across the university's various branding activities. The findings reveal significant variations in font application, particularly in promotional materials and academic events. The study concludes that the adaptability and diversity of Chinese variable logo fonts are key to strengthening the university's brand identity, contributing to a more cohesive and dynamic branding strategy. This research offers valuable insights for educational institutions seeking to enhance their branding through innovative typographic solutions, emphasizing the practical relevance of flexible, culturally resonant design elements.